Social Reality in The Local Cultural Wisdom of The Tenggerese Community as Natural Disaster Education - Aminkun Imam Rafii; Sarmini; Sukma Perdana Prasetya; Abdul Khamid (International Journal of Geography, Social, and Multicultural Education, 2023)
This study aims to explore various social realities that occur in the Tengger Community which are local cultural wisdom as an effort to mitigate natural disasters. This research method uses a qualitative approach through data collection techniques consisting of interviews, observation and documentation. The interviews included 8 important figures in the Tengger community who are trusted by the community in protecting their territory. Data analysis techniques go through three main stages, namely: Data Reduction, Data Presentation, Drawing Conclusions and Verification. The results of this study conclude that natural disaster education is one of the steps for disaster management that takes into account local wisdom and traditional knowledge that exist and develop in society